Ответ(ы) на вопрос:
Гость
[latex]1)\; \; \; \left (( \frac{1}{25} )^{-\frac{1}{2}}\cdot 7^{-1}-(\frac{1}{8})^{-\frac{1}{3}}\cdot 2^{-3}\right ):49^{-\frac{1}{2}}=\\\\=\left (25^{\frac{1}{2}}\cdot \frac{1}{7}-8^{\frac{1}{3}}\cdot (\frac{1}{2})^3}}\right ):\frac{1}{49^{\frac{1}{2}}}=(5\cdot \frac{1}{7}-2\cdot \frac{1}{8}):\frac{1}{7}=\\\\=(\frac{5}{7}-\frac{1}{4})\cdot 7= \frac{20-7}{7\cdot 4}\cdot 7= \frac{13}{4} [/latex]
[latex]2)\; \; \; \frac{8^{-\frac{1}{3}}\cdot 25^{-\frac{1}{2}}-2^{-1}}{64^{\frac{1}{4}}\cdot 2^{\frac{1}{2}}}=\frac{\frac{1}{2}\cdot \frac{1}{5}-\frac{1}{2}}{2^{\frac{3}{2}}\cdot 2^{\frac{1}{2}}}=\\\\=\frac{\frac{1}{2}\cdot (\frac{1}{5}-1)}{2^2}=-\frac{4}{5}\cdot \frac{1}{2^3}=-\frac{4}{5\cdot 2^3}=-\frac{1}{5\cdot 2} =-\frac{1}{10}=-0,1[/latex]
Не нашли ответ?
Похожие вопросы